PENGARUH CONSUMER INVOLVEMENT, KREDIBILITAS SUMBER INFORMASI, TERHADAP REPUCHASE INTENTIONS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi kasus pengguna aplikasi shopee pada mahasiswa Universitas Sarjanawiyata Tamansiswa)” - Marnuti Eka Putri (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to see whether there is an effect of consumer involvement. The first one affects customer satisfaction, the second is the credibility effect of information sources on customer satisfaction, the third is the influence of consumer influence on Repurchase Intention, the fourth is the influence of credibility of information sources. Consumers on Repurchase Intention Decisions, Sixth Influence of Consumer Involvement in Repurchase Decisions through Customer Satisfaction and the seventh has an influence on the credibility of information sources and consumer satisfaction of repurchase decisions The sample in this study was 100 students of Universitas Sarjanawiyata Tamansiswa Yogyakarta who have used the shopee application. Data collection method using questionnaire method shared using Accidental Purposive Sampling technique. In this study used Data Quality Test, Classic Assumption Test, Multiple Regression Test and Sobel Test.The results The first consumer involvement affects consumer satisfaction in shopee application users of Sarjanawiyata Tamansiswa University students, the second is the influence of the credibility of information sources on customer satisfaction on shopee application users of Sarjanawiyata Tamansiswa University students, the third is the influence of the influence of consumer involvement on Repurchase Intention on shopee application users of Sarjanawiyata Tamansiswa University students, The fourth is the influence of the credibility of the information source Repurchase Intention Intention of the shopee application of the Sarjanawiyata Tamansiswa University students, fifth there is an influence of consumer satisfaction on the decision of Repurchase Intention on shopee application users of the University of Sarjanawiyata Tamansiswa, the sixth is the influence of the consumer involvement in the decision to repurchase through customer satisfaction on the shopee application users of University students Sarjanawiyata Tamansiswa and the seventh have an influence on the credibility of information sources dap consumer satisfaction repurchase decisions on shopee application users of Sarjanawiyata University students